Effect Of Water Injection Inside A Double Walled Throatless Downdraft Gasifier For Improving Producer Gas Quality - Amat Sazali , Shazrul Nizam (2015)
Biomass had been proven of its potential as an alternative energy since non-renewable energy such as fossil fuels are undergoing depletion and price increase. The quality of the producer gas using air as gasifying agent has a relatively low heating value of 4-5 MJ/Nm3. Steam gasification produces better producer gas in quality compared to normal air gasification but requires a steam generator which uses a lot of power to generate the steam. Water injection method had been proposed in order to enhance the producer gas quality by increasing the hydrogen content and heating value thus directly increases the quality of the producer gas. A double walled throatless downdraft gasifier (DWTD) was used in the study. Water is injected into the annulus of the gasifier that separates the bed and the air supply. Theoretically, the water injected into the gasifier will be converted into superheated steam by the heat from the wall of the gasifier. So, steam to biomass (S/B) ratio has been introduced to investigate the optimum amount of water needed to be injected for a specific amount of biomass that produces the optimum quality of producer gas. Comparisons were made on the composition and heating value of the producer gas with and without water injection which were analyzed and calculated with the aid of a gas chromatograph. Heating value of the producer gas with the optimum S/B ratio of 0.2 was found to be 4.87 MJ/Nm3 with approximately 10% increment in the overall gas performance. Various S/B ratios were investigated in this study with the range from 0.1 to 0.3. However, as S/B ratio goes higher than 0.25, it results adversely to the quality of the producer gas. The effect of water injection on tar was also investigated in this experiment. Higher S/B ratio had resulted in lower tar concentration in the producer gas. The optimum S/B ratio of 0.2 has given a tar yield of 0.675 g/m3, which is 4.26% reduction.